Peran Manajemen Risiko dalam Pencegahan Kesalahan Medik (Medical Error) di Rumah Sakit - Safidni, Elvira; Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Medical errors are a serious challenge in the healthcare system that can negatively impact patient safety and the hospital's reputation. The implementation of risk management is a strategic approach to identifying, analyzing, and controlling potential medical errors. Objective: To explain and analyze the role of risk management in preventing medical errors in hospitals. Methods: This study used a descriptive qualitative method with a case study approach in a type B hospital in Indonesia. Data were obtained through in-depth interviews with the risk management team, observations, and a review of internal hospital documents. Data analysis used triangulation techniques. Results: The results indicate that risk management in the hospital has been implemented in the form of clinical risk identification, incident reporting, root cause analysis, and the implementation of prevention policies. However, challenges remain, including a weak reporting culture and a lack of regular training for healthcare workers. Conclusion: Risk management plays a critical role in preventing medical errors. Strengthening a patient safety culture, routine training, and a safe and non-punitive incident reporting system are needed to encourage continuous improvement.